PENERAPAN ALGORITMA APRIORI DALAM MENENTUKAN TREND PENJUALAN MOBIL PADA RODA MAS SUZUKI - ceni kirani valensyah; Tukino Tukino (Universitas Putera Batam, 2025)
This study aims to understand the process of data analysis using the Apriori Algorithm to determine sales levels, identify trends in car sales to boost sales, and develop sales strategies. It focuses on identifying trends and sales patterns of cars at Roda Mas Suzuki, applying the Apriori algorithm to uncover associations between sold car types, and providing data-driven recommendations to management for more effective sales strategies.The research employs a quantitative method using the Apriori algorithm. The findings reveal that data mining association rules can be utilized to manage and leverage data to enhance sales strategies. Based on the 2024 Roda Mas Suzuki sales data, the combinations with the highest support and confidence values are NEW CARRY PICK UP - NEW XL 7 (24.11%-50.94%) and ALL NEW ERTIGA - NEW CARRY PICK UP (23.21%-50%).This analysis can assist in managing stock for marketing purposes, preventing the accumulation of less demanded products, which could lead to future losses. The Apriori algorithm in this study proves effective in identifying frequently purchased product combinations by consumers, providing valuable insights to Roda Mas Suzuki for optimizing their marketing strategies.